Education Role in Stunting Under Two Years among Poor Communities in Indonesia - Yunitawati, Diah; Laksono, Agung Dwi; Khairunnisa, Marizka; Purwoko, Sidiq; Wulandari Muis, Early; Nursafingi, Afi; Riyanto, Slamet; Samsudin, Mohamad (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Indonesia still has a stunting problem, even though the stunting rate has decreased. The study analyses the association of the maternal education level with the incidence of stunted children under the age of two in poor communities in Indonesia.Method: The cross-sectional data from the Indonesian National Nutritional Status Survey 2021 examined 24,920 children under two years old. The relationship between the variables was tested using binary logistic regression.Result: The odds of having stunted children below the age of two are 1.705 times greater for women with no education than women with higher levels of education (AOR 1.705; 95% CI 1.667-1.744). Primary-educated mothers were 1.178 times increased risk of having stunted children under age two compared to higher-educated mothers (AOR 1.178; 95% CI 1.157-1.199). The study analysis found no significant difference between secondary and higher education to have stunted children. In addition to education level, the study also identified six other important control variables associated with stunting in children under the age of two: residence location, age of mother, married status, child's age, child's gender, and EIBF. According to the study's findings, stunting in children under the age of two is related to maternal educational levels among Indonesia's poor communities. An increased incidence of stunting in children under the age of two is associated with lower levels of maternal education.